Effect of a fetal surveillance unit on admission of antenatal patients to hospital. - Soothill, P W (1991)
OBJECTIVE--To analyse the effect of a fetal surveillance unit, which undertakes a wide range of maternal and fetal tests on an outpatient or inpatient basis, on the number and length of antenatal hospital admissions. DESIGN--A comparison of the number and length of antenatal admissions six months before and five months after the opening of the unit on 1 July 1990. MAIN OUTCOME MEASURES--Admission rate, antenatal bed occupancy, and interval from admission to discharge or delivery. RESULTS--The antenatal bed occupancy rate fell by 22% from 174/100 deliveries during the six months before the unit was opened to 136/100 deliveries in the five months after it was opened. The difference in distribution of lengths of admission after the unit was opened from before was highly significant (Mann-Whitney test = 5.14, n = 752 and 679; p less than 0.0001), and this was due to shorter intervals from admission to discharge and from admission to delivery. In contrast, the antenatal admission rate did not change significantly (50/100 deliveries v 49/100 deliveries). There was no significant change in the stillbirth rate (6/1294 births v 8/1372 births; difference between rates = 0.0012, 95% confidence interval-0.0043 to 0.0067). CONCLUSION--Obstetricians are more prepared to discharge antenatal patients from hospital and, similarly, admit patients for delivery rather than for assessment if the patients are reliably monitored on an outpatient basis. If this change in practice is sustained substantial financial and social benefits will result as well as improvements in organisation, audit, teaching, and research.